The Influence Of Perceived Ease Of Use On The Intention To Use Digital Payment Applications In Transactions - Purwanto, Hendra; Adi, Handaru Indrian Sasmito; Astuty, Henny Sri; Suwarno (Universitas Indo Global Mandiri, 2024)
In the digital era, technology has advanced rapidly, including in Indonesia. One significant innovation is the use of digital payment applications such as OVO, DANA, GoPay, and others, which facilitate daily transactions without the need for cash. This study employs a library research method to examine the influence of perceived ease of use and perceived usefulness on the intention to use digital payment applications. Based on simultaneous testing results, both perceived ease of use and perceived usefulness positively impact the decision to adopt these applications. This finding aligns with the study by Arif et al. (2022), which demonstrated that positive perceptions of technology significantly influence application adoption. Digital payment applications offer several advantages, including convenience, time efficiency, and enhanced security compared to cash transactions. Additional features such as promotions, cashback, and integration with other platforms further enhance user appeal. This research supports the Technology Acceptance Model (TAM), emphasizing the critical role of perceived ease of use and usefulness in driving the adoption of new technologies. Furthermore, these technologies align with governmental policies promoting financial inclusion and the establishment of a cashless society. The continuous development of these applications is expected to improve efficiency and convenience in Indonesia's payment systems. These findings have practical implications for application developers to enhance user interfaces, system reliability, and feature innovations to expand market share. Overall, digital payment applications play a crucial role in supporting Indonesia's digital economic transformation and serve as a foundation for marketing strategies and public policies regarding financial inclusion. Keywords: Perceived Ease of Use, Interest in Use, Digital Payment Applications, Transactions.